COVID-19 severity correlates with airway epithelium-immune cell interactions identified by single-cell analysis - Chua, Robert Lorenz; Lukassen, Soeren; Trump, Saskia; Hennig, Bianca P.; Wendisch, Daniel; Pott, Fabian; Debnath, Olivia; Thürmann, Loreen; Kurth, Florian; Völker, Maria Theresa; Kazmierski, Julia; Timmermann, Bernd; et al. (Nature biotechnology, 2020)
To investigate the immune response and mechanisms associated with severe coronavirus disease 2019 (COVID-19), we performed single-cell RNA sequencing on nasopharyngeal and bronchial samples from 19 clinically well-characterized patients with moderate or critical disease and from five healthy controls. We identified airway epithelial cell types and states vulnerable to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. In patients with COVID-19, epithelial cells showed an average three-fold increase in expression of the SARS-CoV-2 entry receptor ACE2, which correlated with interferon signals by immune cells. Compared to moderate cases, critical cases exhibited stronger interactions between epithelial and immune cells, as indicated by ligand-receptor expression profiles, and activated immune cells, including inflammatory macrophages expressing CCL2, CCL3, CCL20, CXCL1, CXCL3, CXCL10, IL8, IL1B and TNF. The transcriptional differences in critical cases compared to moderate cases likely contribute to clinical observations of heightened inflammatory tissue damage, lung injury and respiratory failure. Our data suggest that pharmacologic inhibition of the CCR1 and/or CCR5 pathways might suppress immune hyperactivation in critical COVID-19.
Das PDF enthält zusätzlich einen Anhang von 15 Seiten
Gesehen am 29.06.2020